Biased technological change and employment reallocation - Zsófia L. Bárány; Christian Siegel (University of Kent, School of Economics, 2018)
To study the drivers of the employment reallocation across sectors and occupations between 1960 and 2010 in the US we propose a model where technology evolves at the sector-occupation cell level. This framework allows us to quantify the bias of technology across sectors and across occupations. We implement a novel method to extract changes in sector-occupation cell productivities from the data. Using a factor model we find that occupation and sector factors jointly explain 74-87 percent of cell productivity changes, with the occupation component being by far the most important. While in our general equilibrium model both factors imply similar reallocations of labor across sectors and occupations, quantitatively the bias in technological change across occupations is much more important than the bias across sectors.
Keywords: O41; O33; J24; 330; biased technological change; structural change; employment polarization